Relationship between situational inhibitors and informal learning amongst accountants - Mat Samsudin, Mohd Amir; Saad, Ram Al Jaffri; Selamat, Mohamad Hisyam; Syahir, Abdul Wahab (CSRC Publishing, 2017)
Purpose: Informal learning activities are important for chartered accountants in public accounting firms to develop and maintain knowledge and skills within the professional environment. However, recent evidence indicates that situational inhibitors to the learning exist in their working environment. Thus, the objective of this research is to examine the relationship between situational inhibitors and informal learning activities amongst the accountants.Design/Methodology/Approach: A total of 260 chartered accountants in the firms across Malaysia participated in this study. The data of the study was collected through mail survey approach and analysed using correlation analysis.Findings: The findings indicated that lack of time and lack of support from others inhibited the accountants' informal workplace learning activities. The evidence suggests that accountants who face these two constraints at the workplace, would be less likely to engage in informal learning activities.Implications/Originality/Value: This study adds to previous literature by testing the relationship between situational inhibitors and the accountants' informal learning activities. Practically, the research findings are critical for accounting profession in developing appropriate strategies to overcome the identified problems.